A PROSPEROUS NEIGHBORHOOD AND VILLAGE PEOPLE WILL HAVE A PROSPEROUS HEART AND A HIGH CULTURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The initiative implemented within the framework of the criteria of the President of the Republic of Uzbekistan "A safe house, a safe street, a safe neighborhood" is welcomed and supported by our people with great joy. In order to find timely and high-quality solutions to the problems of the population, the representatives of the working group are conducting house-to-house studies. Each house is paid attention to, kitchens and ovens are put in order, walls are painted, trees are shaped, fields are plowed, streets are cleaned together with the owners of the house.